The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/ajp.0000000000001008
|View full text |Cite
|
Sign up to set email alerts
|

Are Changes in Sleep Quality/Quantity or Baseline Sleep Parameters Related to Changes in Clinical Outcomes in Patients With Nonspecific Chronic Low Back Pain?

Abstract: Objectives: Sleep disturbance is prevalent among patients with chronic low back pain (CLBP). This systematic review aimed to summarize the evidence regarding the: (1) temporal relations between changes in sleep quality/quantity and the corresponding changes in pain and/or disability; and (2) role of baseline sleep quality/quantity in predicting future pain and/or disability in patients with CLBP.Methods: Four databases were searched from their inception to February 2021. Two reviewers independently screened th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 102 publications
2
9
0
Order By: Relevance
“…Our findings also suggest that insomnia is one of the significant predictors of pain intensity in people with CLBP, which concurs with previous research that higher ISI scores were associated with higher pain intensity in people with CLBP (88). Similarly, a recent systematic review revealed low-to moderate-quality evidence that improved sleep quantity/quality is significantly related to improved LBP-related disability or reduced LBP in patients with CLBP (89). However, sleep disturbances and pain may affect each other reciprocally to form a vicious cycle because some brain regions (e.g., mesencephalic periaqueductal gray, thalamus, and raphe magnus) responsible for the initiation and maintenance of sleep are also involved in pain modulation (90).…”
Section: Insomniasupporting
confidence: 92%
“…Our findings also suggest that insomnia is one of the significant predictors of pain intensity in people with CLBP, which concurs with previous research that higher ISI scores were associated with higher pain intensity in people with CLBP (88). Similarly, a recent systematic review revealed low-to moderate-quality evidence that improved sleep quantity/quality is significantly related to improved LBP-related disability or reduced LBP in patients with CLBP (89). However, sleep disturbances and pain may affect each other reciprocally to form a vicious cycle because some brain regions (e.g., mesencephalic periaqueductal gray, thalamus, and raphe magnus) responsible for the initiation and maintenance of sleep are also involved in pain modulation (90).…”
Section: Insomniasupporting
confidence: 92%
“…Most of our participants reported sleep disturbance, which interfered with their daily routine and emotions. Research has suggested that poor sleep aggravated pain by sensitizing pain perception, [ 32 ] while pain can also interfere with one’s sleep quality [ 33 ], resulting in a vicious circle [ 34 ]. Additionally, sleep disturbance can be a major source of psychological distress in people with chronic pain [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review focusing on sleep disruption and chronic low back pain, it was observed that improvements in self-reported sleep duration and quality were significantly associated with improvements in lower back pain 13. In elderly patients undergoing lumbar spinal surgery, postoperative improvement in sleep quality has been demonstrated to correlate with improvements in disability 14.…”
Section: Sleep Quality and Spine Surgerymentioning
confidence: 99%